2014
DOI: 10.1007/s12020-014-0490-9
|View full text |Cite
|
Sign up to set email alerts
|

Incretin-based therapies and pancreatitis risk: myth or reality

Abstract: Incretins are gastrointestinal hormones secreted in response to food intake that modify biological mechanisms of glucose homeostasis in the body. Approximately 70 % of insulin secretion by pancreatic b-cells is under the control of two incretin molecules, namely glucose-dependent intestinal polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) [1]. Endogenous GLP-1 is rapidly degraded by the enzyme dipeptidyl peptidase-4 (DPP-4) to an inactive molecule that terminates its incretin effect. Research on the pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Pancreatitis cases have been reported in animals and in humans treated with agents of this class. Exenatide and Liraglutide are associated with reported cases of acute pancreatitis, whereas lixisenatide has not, so far [64]. Studies show an average incidence of 1.6 cases of acute pancreatitis per 1000 patients/years of exposure, as for Liraglutide [65].…”
Section: Side Effects and Associated Risks Of Glp-1 Agonists Receptormentioning
confidence: 99%
“…Pancreatitis cases have been reported in animals and in humans treated with agents of this class. Exenatide and Liraglutide are associated with reported cases of acute pancreatitis, whereas lixisenatide has not, so far [64]. Studies show an average incidence of 1.6 cases of acute pancreatitis per 1000 patients/years of exposure, as for Liraglutide [65].…”
Section: Side Effects and Associated Risks Of Glp-1 Agonists Receptormentioning
confidence: 99%
“…One observational study found that current use of sitagliptin or exenatide was significantly associated with risk of hospitalization for acute pancreatitis; however, a systematic review and meta‐analysis, including 9 studies, with >1.3 million individuals and an average follow‐up of 0.7 to 1.4 years, found that incretin‐based therapy did not increase the risk of pancreatitis . Multiple observational studies have assessed the association between incretin‐based therapy and pancreatitis . Given the controversy, the European Medicines Agency and the US Food and Drug Administration have called for additional studies …”
Section: Introductionmentioning
confidence: 99%
“…13 Multiple observational studies have assessed the association between incretin-based therapy and pancreatitis. [14][15][16][17] Given the controversy, the European Medicines Agency and the US Food and Drug Administration have called for additional studies. [18][19][20] Furthermore, in contrast to the risk of acute pancreatitis, the risk of chronic pancreatitis with incretin use has not been investigated in an observational setting.…”
Section: Introductionmentioning
confidence: 99%